[Subok na matibay; Purple haze; Music time - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Documents Banco Filipino and Central Bank's closure order; hazing initiations in fraternities and interview with Jo Awayan.
Subok na matibay (20 min.) -- Purple Haze (20 min.) -- Music Time (15 min.).
VHS.
Keywords: Awayan, Jo. Interviews; Banco Filipino; Hazing; Greek letter societies; Initiations (into trade, societies, etc.).